Application of the Risk Principle in the Supervision and Treatment of Individuals Who Have Sexually Offended: Does “Oversupervision” Matter? - Pederson, Kaitlyn M. (Criminal justice and behavior, 2022)
Individuals who sexually offend are commonly misunderstood as being high risk. According to the risk–need–responsivity (RNR) principles, treatment and supervision levels should be determined by actuarial risk for the best outcomes. To date, no studies have examined these principles with individuals on supervision for a sexual offense. This study applies the RNR principles to a sample of 133 men and women serving probated sentences for a sexual offense and mandated to specialized treatment. Results indicate low-risk individuals convicted of a sexual offense were more likely to be compliant with probation and treatment than moderate-risk individuals. An analysis of risk level and supervision overrides (N = 75) provides support for the prediction that low-risk individuals supervised at high levels may be more likely to have compliance problems. Results suggest similar outcomes when violating the risk principle for individuals who have sexually offended to the findings among general justice-involved people.